Zinc air battery
By designing the negative electrode of the metal zinc paste battery with a 9-grid grid structure and the air electrode carbon sheet with a waterproof and breathable membrane in the zinc air battery, the problems of electrolyte leakage and insufficient energy density are solved, and high energy density and excellent discharge performance are achieved.
Patent Information
- Application Number
- CN202411148628.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-21
AI Technical Summary
In practical applications, zinc air batteries are prone to electrolyte leakage problems, resulting in battery failure or even damage to electrical devices, and the energy density needs to be improved.
A zinc-air battery is designed, which includes a first air electrode carbon sheet, a first positive electrode sheet, a metal zinc paste battery cell negative electrode, a second positive electrode sheet, a second air electrode carbon sheet and a semi-solid electrolyte arranged in sequence. The negative electrode of the metal zinc paste battery core is wrapped by a shell with a 9-grid grid structure, and contains a waterproof and breathable membrane and a support skeleton of the catalyst to ensure the maximum contact area between the electrolyte and the air electrode carbon sheet.
This design significantly improves the energy density and discharge performance of zinc air batteries, and can achieve a specific capacity of more than 700Ah/kg and a discharge energy density of more than 670Wh/kg under a constant voltage of 0.9V, while ensuring the liquid leakage resistance of the battery.
Smart Images

Figure CN119542625A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc-air batteries, and in particular to a zinc-air battery. Background Art
[0002] Zinc-air battery (ZAB) is a metal-air battery that uses oxygen in the air as the positive electrode and zinc as the negative electrode to provide energy. The capacity consumption of the zinc-air battery after storage can be maintained within 5% per year, and it has low self-reaction. The significant features such as large capacity, high safety, low self-discharge and low cost make it an important battery form.
[0003] In the current commercialization process, zinc-air batteries mainly use convenient and reliable alkaline aqueous solution systems as electrolytes in practical applications. The most critical issue is how to ensure the battery's resistance to leakage. Since zinc-air batteries need to be exposed to the outside air, they have an inherently open structure, so in actual use, electrolyte leakage is very likely to occur, causing battery failure or even damage to electrical devices; at the same time, the energy density needs to be further improved. Summary of the invention
[0004] The object of the present invention is to provide a zinc-air battery, which has a higher energy density and is less likely to cause the problem of electrolyte leakage.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a zinc-air battery, comprising a first air electrode carbon sheet, a first positive electrode sheet, a metal zinc paste battery negative electrode, a second positive electrode sheet, a second air electrode carbon sheet and an electrolyte, which are arranged in sequence;
[0007] The electrolyte is filled in the entire cavity of the zinc-air battery;
[0008] The negative electrode of the metal zinc paste battery cell comprises a metal current collector and a first zinc electrode and a second zinc electrode respectively arranged on both sides of the metal current collector;
[0009] The raw material for preparing the first zinc electrode or the second zinc electrode is metal zinc paste; the raw material for preparing the metal zinc paste consists of zinc powder, gel and water;
[0010] The electrolyte is a semi-solid electrolyte;
[0011] The first air electrode carbon sheet and the second air electrode carbon sheet both include a waterproof breathable membrane and a support skeleton with a catalyst on the surface, and the waterproof breathable membrane and the support skeleton with a catalyst on the surface are pressed together;
[0012] The negative electrode of the metal zinc paste battery cell is wrapped by a shell with 9-grid windows;
[0013] The negative electrode of the metal zinc paste battery cell is a 9-grid grid structure, and the 9-grid grid structure is consistent with the reinforcing ribs of the 9-grid window openings of the shell;
[0014] It also includes a window cover plate, which includes a front cover, a rear cover and an upper cover; the window cover plate is located at the outermost side of the zinc-air battery, and the front cover and the rear cover of the window cover plate are 8-grid windows.
[0015] Preferably, the negative electrode of the metal zinc paste battery cell includes two tabs, and the tabs are not wrapped by the shell with 9-grid windows and extend to the outside of the zinc-air battery.
[0016] Preferably, the inner side section of the shell is provided with side steps and positioning posts for fixing the negative electrode of the metal zinc paste battery cell;
[0017] The outer side of the shell is provided with a sunken step for placing the first positive electrode sheet and the second positive electrode sheet.
[0018] Preferably, the first positive electrode sheet and the second positive electrode sheet each include two tabs, and the tabs extend to the outside of the zinc-air battery.
[0019] Preferably, the method for preparing the negative electrode of the metal zinc paste battery cell comprises the following steps:
[0020] Mix zinc powder, gel and water to make zinc paste;
[0021] The zinc paste is coated on both sides of the metal current collector to obtain the negative electrode of the metal zinc paste battery.
[0022] Preferably, the mass ratio of the zinc powder, gel and water is 30:(1-1.2):(5-6);
[0023] The gel comprises one or more of food starch glue, polyacrylamide, polyvinyl acetate, sodium carboxymethyl cellulose and polyurethane.
[0024] Preferably, the method for preparing the semi-solid electrolyte comprises the following steps:
[0025] After mixing potassium hydroxide, water and gel powder, the mixture is allowed to stand to obtain the semi-solid electrolyte;
[0026] The mass ratio of the potassium hydroxide, water and gel powder is 345:1000:3.
[0027] Preferably, the gel powder comprises one or more of silicon dioxide, water-absorbing resin SAP, agar, potassium alginate, sodium alginate, polyacrylamide and a dispersant.
[0028] Preferably, the method for preparing the first air electrode carbon sheet or the second air electrode carbon sheet comprises the following steps:
[0029] mixing carbon powder, graphite, metal oxide and platinum to obtain a mixed catalyst;
[0030] Mixing the mixed catalyst, polytetrafluoroethylene solution and diluent to obtain a catalyst dispersion;
[0031] After the support skeleton is immersed in the catalyst dispersion, it is pressed with the waterproof breathable membrane to obtain the first air electrode carbon sheet or the second air electrode carbon sheet.
[0032] Preferably, the mass ratio of the carbon powder, graphite, metal oxide and platinum is (68-70):(19-20):(10-15):(2-3);
[0033] The carbon powder is one or more of superconductive carbon powder, activated carbon, carbon black and acetylene black;
[0034] The mass ratio of the mixed catalyst, the polytetrafluoroethylene solution and the diluent is (65-70): (5-6): (20-30), and the mass concentration of the polytetrafluoroethylene solution is 45%-60%.
[0035] The invention provides a zinc-air battery, comprising a first air electrode carbon sheet, a first positive electrode sheet, a metal zinc paste battery negative electrode, a second positive electrode sheet, a second air electrode carbon sheet and an electrolyte which are sequentially stacked; the electrolyte is filled in the entire cavity of the zinc-air battery; the metal zinc paste battery negative electrode comprises a metal current collector and a first zinc electrode and a second zinc electrode which are respectively arranged on both sides of the metal current collector; the raw material for preparing the first zinc electrode or the second zinc electrode is metal zinc paste; the raw material for preparing the metal zinc paste consists of zinc powder, gel and water; the electrolyte is a semi-solid electrolyte; The first air electrode carbon sheet and the second air electrode carbon sheet both include a waterproof and breathable membrane and a supporting skeleton with a catalyst on the surface, and the waterproof and breathable membrane is pressed together with the supporting skeleton with a catalyst on the surface; the negative electrode of the metal zinc paste battery cell is wrapped by a shell with a 9-grid window; the negative electrode of the metal zinc paste battery cell is a 9-grid grid structure, and the 9-grid grid structure is consistent with the reinforcement ribs of the 9-grid window of the shell; it also includes a window cover plate, and the window cover plate includes a front cover, a rear cover and an upper cover; the window cover plate is located at the outermost side of the zinc-air battery, and the front cover and the rear cover of the window cover plate are 8-grid windows. The air electrode sheet in the zinc-air battery of the present invention has a waterproof and breathable function, and the structural design of the zinc-air battery can ensure that more air enters, so that the contact area between the air electrode sheet and the electrolyte is maximized, and both sides of the negative electrode of the metal zinc paste battery cell can fully react, which makes the zinc-air battery of this structure have excellent discharge performance. When the voltage is kept at a constant voltage of 0.9V, the specific capacity can reach more than 700Ah / kg, the discharge energy density can reach more than 670Wh / kg, the 24h current is more than 3A, and the 72h current is more than 1A. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the structure of the zinc-air battery of the present invention;
[0037] Figure 2 This is a 3D exploded view of the zinc-air battery of the present invention without the negative electrode of the metal zinc paste battery cell;
[0038] Figure 3 This is a schematic diagram of the position structure of the side steps and the positioning posts in the housing of the zinc-air battery of the present invention;
[0039] Figure 4 This is a schematic diagram of the position structure of the sunken step in the shell of the zinc-air battery of the present invention;
[0040] Figure 5 It is a partial cross-sectional structural schematic diagram of the zinc-air battery of the present invention (including the front cover, the first air electrode carbon sheet and the first positive electrode sheet);
[0041] Figure 6This is the discharge voltage-current specific energy capacity curve of the zinc-air battery described in Example 1.
[0042] Among them, 1 is the first air electrode carbon sheet, 2 is the first positive electrode sheet, 3 is the first zinc electrode, 4 is the negative electrode of the metal zinc paste battery cell, 5 is the second zinc electrode, 6 is the second positive electrode sheet, 7 is the second air electrode carbon sheet, 8 is the electrolyte, 9 is the upper cover, 10 is the front cover including the first air electrode carbon sheet, 11 is the shell package with 9 grid windows, 12 is the back cover including the second air electrode carbon sheet, 13 is the side step, 14 is the battery cell negative electrode positioning column, and 15 is the sinking step. DETAILED DESCRIPTION
[0043] The present invention provides a zinc-air battery, comprising a first air electrode carbon sheet, a first positive electrode sheet, a metal zinc paste battery negative electrode, a second positive electrode sheet, a second air electrode carbon sheet and an electrolyte, which are arranged in sequence;
[0044] The electrolyte is filled in the entire cavity of the zinc-air battery (eg Figure 1 shown);
[0045] The negative electrode of the metal zinc paste battery cell comprises a metal current collector and a first zinc electrode and a second zinc electrode (such as Figure 1 shown);
[0046] The raw material for preparing the first zinc electrode or the second zinc electrode is metal zinc paste; the raw material for preparing the metal zinc paste consists of zinc powder, gel and water;
[0047] The electrolyte is a semi-solid electrolyte;
[0048] The first air electrode carbon sheet and the second air electrode carbon sheet both include a waterproof breathable membrane and a support skeleton with a catalyst on the surface, and the waterproof breathable membrane and the support skeleton with a catalyst on the surface are pressed together;
[0049] The negative electrode of the metal zinc paste battery cell is wrapped by a shell with 9 grid windows (such as Figure 2 shown);
[0050] The negative electrode of the metal zinc paste battery cell is a 9-grid grid structure, and the 9-grid grid structure is consistent with the reinforcing ribs of the 9-grid window openings of the shell;
[0051] It also includes a window cover plate, which includes a front cover, a rear cover and an upper cover; the window cover plate is located at the outermost side of the zinc-air battery, and the front cover and the rear cover of the window cover plate are 8-grid windows (such as Figure 2 shown).
[0052] In the present invention, the 9-grid grid structure can greatly increase the contact surface between the electrolyte and the catalyst in the air electrode carbon sheet. The 8-grid window opening can greatly increase the air inlet surface.
[0053] In the present invention, the negative electrode of the metal zinc paste battery cell preferably includes two tabs, and the tabs are not wrapped by the shell with 9-grid windows and extend to the outside of the zinc-air battery. In the present invention, the role of the tabs is to facilitate the series and parallel connection between battery cells.
[0054] In the present invention, the inner side section of the shell is preferably provided with side steps and positioning columns (such as Figure 3 The outer side of the shell is preferably provided with a sunken step (as shown) for placing the first positive electrode sheet and the second positive electrode sheet Figure 4 In the present invention, the sinking height of the sinking step is preferably 2 mm. A sealing silicone pad is also preferably placed on the sinking step.
[0055] In the present invention, the first positive electrode sheet and the second positive electrode sheet preferably each include two tabs, and the tabs extend to the outside of the zinc-air battery.
[0056] In the present invention, the zinc-air battery is preferably a rectangular parallelepiped structure.
[0057] In the present invention, the method for preparing the negative electrode of the metal zinc paste battery cell comprises the following steps:
[0058] Mix zinc powder, gel and water to make zinc paste;
[0059] The zinc paste is coated on both sides of the metal current collector to obtain the negative electrode of the metal zinc paste battery.
[0060] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0061] The invention mixes zinc powder, gel and water to obtain zinc paste.
[0062] In the present invention, the mass ratio of the zinc powder, gel and water is preferably 30:(1-1.2):(5-6), more preferably 30:(1-1.1):5, and most preferably 30:1:5.
[0063] In the present invention, the gel preferably includes one or more of food starch glue, polyacrylamide, polyvinyl acetate, sodium carboxymethyl cellulose and polyurethane. When the gel is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, the water is preferably deionized water.
[0064] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0065] After the zinc paste is obtained, the present invention applies the zinc paste on both sides of the metal current collector to obtain the negative electrode of the metal zinc paste battery cell.
[0066] In the present invention, the material of the metal current collector is preferably 304 stainless steel sheet. In the present invention, the metal current collector preferably includes two tabs.
[0067] The present invention does not have any special limitation on the coating process, and the coating process may be carried out by a process well known to those skilled in the art and it may be ensured that the tabs in the metal current collector are not coated during the coating process.
[0068] In the present invention, the coating thickness is preferably 1 to 2 mm, more preferably 1 to 1.5 mm, and most preferably 1.5 mm.
[0069] After the coating is completed, the present invention further preferably includes drying, and the drying temperature is preferably 70° C. and the drying time is preferably 2 hours. In the present invention, the drying is preferably carried out in an oven.
[0070] In the present invention, the first positive electrode sheet and the second positive electrode sheet are preferably 304 stainless steel sheets, which are cut into 9-grids by laser, and the 9-grids are consistent with the shell, leaving 2 tabs.
[0071] In the present invention, the method for preparing the first air electrode carbon sheet and the second air electrode carbon sheet comprises the following steps:
[0072] mixing carbon powder, graphite, metal oxide and platinum to obtain a mixed catalyst;
[0073] Mixing the mixed catalyst, polytetrafluoroethylene solution and diluent to obtain a catalyst dispersion;
[0074] After the support skeleton is immersed in the catalyst dispersion, it is pressed with the waterproof breathable membrane to obtain the first air electrode carbon sheet and the second air electrode carbon sheet.
[0075] The present invention mixes carbon powder, graphite, metal oxide and platinum to obtain a mixed catalyst.
[0076] In the present invention, the mass ratio of the carbon powder, graphite, metal oxide and platinum is preferably (68-70):(19-20):(10-15):(2-3), more preferably (68-70):19:(10-12):3, and most preferably 68:19:10:3.
[0077] In the present invention, the carbon powder is preferably one or more of superconducting carbon powder, activated carbon, carbon black and acetylene black. When the carbon powder is two or more of the above specific selections, the present invention has no special limitation on the ratio of the above specific substances, and they can be mixed in any ratio.
[0078] In the present invention, the metal oxide preferably includes one or more of manganese dioxide, copper oxide, silver oxide and cobalt oxide. When the metal oxide is two or more of the above specific selections, the present invention has no special limitation on the ratio of the above specific substances, and they can be mixed in any ratio.
[0079] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0080] After obtaining the mixed catalyst, the present invention mixes the mixed catalyst, polytetrafluoroethylene solution and diluent to obtain a catalyst dispersion.
[0081] In the present invention, the concentration of the polytetrafluoroethylene solution is preferably 45% to 60%, more preferably 50% to 60%, and most preferably 60%.
[0082] In the present invention, the diluent is preferably ethanol and / or ethyl acetate. When the diluent is ethanol and ethyl acetate, the present invention has no special limitation on the ratio of ethanol and ethyl acetate, and they can be mixed in any ratio.
[0083] In the present invention, the mass ratio of the mixed catalyst, polytetrafluoroethylene solution and diluent is preferably (65-70):(5-6):(20-30), more preferably (65-68):(5.5-6)(24-26), and most preferably 70:5.2:24.8.
[0084] In the present invention, the mixing is preferably carried out under stirring conditions, and the stirring speed is preferably 300-500r / min, more preferably 450-500r / min, and most preferably 500r / min; the stirring time is preferably 10-30min, more preferably 20-30min, and most preferably 30min.
[0085] After obtaining the catalyst dispersion, the present invention immerses the support frame in the catalyst dispersion and then presses it with the waterproof breathable membrane to obtain the first air electrode carbon sheet and the second air electrode carbon sheet.
[0086] In the present invention, the support skeleton is preferably nickel foam or stainless steel mesh; the thickness of the nickel foam is preferably 2.5 mm, the pore size of the nickel foam is preferably 75 ppi, the surface density is preferably 480 g, and the thickness is preferably 2.5 mm; the thickness of the stainless steel mesh is preferably 1 mm.
[0087] Before the soaking, the present invention also preferably includes washing and drying the support frame in sequence. In the present invention, the washing is preferably carried out with an organic solvent, and the organic solvent is preferably ethanol. The present invention has no special limitation on the drying process, and the process well known to those skilled in the art can be used.
[0088] The present invention does not have any special limitation on the soaking process, and soaking for 15 minutes may be performed using a process well known to those skilled in the art.
[0089] After the soaking is completed, the present invention also preferably includes air-drying. The present invention has no special limitation on the process of air-drying, and the process well known to those skilled in the art can be used.
[0090] In the present invention, the waterproof and breathable membrane is preferably a polytetrafluoroethylene membrane.
[0091] In the present invention, the pressing pressure is preferably 1-4 MPa, more preferably 1-2 MPa, and most preferably 1 MPa.
[0092] Preferably, the method for preparing the semi-solid electrolyte comprises the following steps:
[0093] After mixing potassium hydroxide, water and gel powder, the mixture is allowed to stand to obtain the semi-solid electrolyte;
[0094] The mass ratio of the potassium hydroxide, water and gel powder is 345:1000:3.
[0095] In the present invention, the purity of the potassium hydroxide is preferably 95%. In the present invention, the water is preferably deionized water. In the present invention, the gel powder preferably includes one or more of silicon dioxide, water-absorbing resin SAP, agar, potassium alginate, sodium alginate, polyacrylamide and dispersant. When the gel powder is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio.
[0096] In the present invention, the mixing is preferably carried out under stirring conditions, the stirring speed is preferably 1000-1500 rpm, more preferably 1200-1500 rpm, most preferably 1500 rpm, and the stirring time is preferably ≥45 min.
[0097] In the present invention, the standing time is preferably 24 hours.
[0098] In the present invention, the preparation method of the zinc-air battery preferably comprises the following steps:
[0099] Take two air electrode carbon sheets (respectively used as the first air electrode carbon sheet and the second air electrode carbon sheet), with the waterproof and breathable membrane of the air electrode carbon sheet facing outward, and stick the air electrode carbon sheets on the front cover and the back cover (8-grid window cover) of the zinc-air battery with glue, and dry them in the shade for 1 hour for later use;
[0100] Take two positive electrode sheets (respectively used as the first positive electrode sheet and the second positive electrode sheet) and two sealing gaskets and glue them to the front and back outer sides of the housing (9-grid structure) of the zinc-air battery, and dry them in the shade for 1 hour for later use;
[0101] Putting the negative electrode of the metal zinc paste battery into the housing of the zinc-air battery and fixing it in the slot position to obtain a housing with a positive electrode and a negative electrode;
[0102] The front cover with the air electrode carbon sheet, the shell with the positive electrode and the negative electrode, and the back cover with the air electrode carbon sheet are assembled in sequence, and then electrolyte is injected and the upper cover is covered to obtain the zinc-air battery.
[0103] The zinc-air battery provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0104] Example 1
[0105] The zinc-air battery structure (rectangular structure) includes: a first air electrode carbon sheet, a first positive electrode sheet (type is 304 stainless steel), a metal zinc paste battery negative electrode, a second positive electrode sheet (type is 304 stainless steel), a second air electrode carbon sheet and an electrolyte which are arranged in sequence; the electrolyte is filled in the entire cavity of the zinc-air battery (such as Figure 1 The negative electrode of the metal zinc paste battery cell includes a metal current collector and a first zinc electrode and a second zinc electrode (as shown in FIG. Figure 1 As shown); the raw material for preparing the first zinc electrode or the second zinc electrode is metal zinc paste; the raw material for preparing the metal zinc paste is composed of zinc powder, gel and water; the electrolyte is a semi-solid electrolyte; the first air electrode carbon sheet and the second air electrode carbon sheet both include a waterproof breathable membrane and a support skeleton containing a catalyst on the surface, and the waterproof breathable membrane is pressed together with the support skeleton containing a catalyst on the surface; the negative electrode of the metal zinc paste battery cell is wrapped by a shell with 9-grid windows (as shown Figure 2As shown); the negative electrode of the metal zinc paste battery cell is a 9-grid grid structure, and the 9-grid grid structure is consistent with the reinforcing ribs of the 9-grid window opening of the shell; it also includes a window cover, and the window cover includes a front cover, a rear cover and an upper cover; the window cover is located at the outermost side of the zinc-air battery, and the front cover and the rear cover of the window cover are 8-grid windows (as shown Figure 2 The negative electrode of the metal zinc paste battery cell includes two tabs, and the tabs are not wrapped by the shell with 9-grid windows and extend to the outside of the zinc-air battery; the inner side section of the shell is provided with side steps and positioning columns (as shown in FIG. Figure 3 The outer side of the shell is provided with a sunken step (as shown) for placing the first positive electrode sheet and the second positive electrode sheet Figure 4 The sinking height of the sinking step is 2 mm. A sealing silicone pad is also placed on the sinking step; the first positive electrode sheet and the second positive electrode sheet each include two tabs, and the tabs extend to the outside of the zinc-air battery;
[0106] Preparation method of the first air electrode carbon sheet and the second air electrode carbon sheet: wash and dry 75ppi 2.5mm thick nickel foam with an organic solvent for standby use; mix and stir 68wt% superconducting carbon powder, 19wt% graphite, 10wt% manganese dioxide and 3wt% platinum for 5 minutes to obtain a catalyst mixture; according to a mass ratio of 70:5.2:24.8, stir the catalyst mixture, a polytetrafluoroethylene solution with a mass concentration of 60% and a diluent (ethanol and ethyl acetate with a mass ratio of 1:1) at a speed of 500r / min for 10 minutes to obtain a mixed solution; soak the pretreated nickel foam in the mixed solution for 15 minutes, lift it up and dry it for 10 minutes, and then press it with a waterproof and breathable membrane (polytetrafluoroethylene membrane) at a pressure of 1MPa to obtain the first air electrode carbon sheet and the second air electrode carbon sheet;
[0107] Preparation method of metal zinc paste battery negative electrode: according to the mass ratio of 30:1:5, metal zinc powder, gel (type is polyacrylamide) and deionized water are mixed to obtain zinc paste; 130g of zinc paste is evenly coated on the front and back sides of a metal current collector (type is 304 stainless steel sheet) with a thickness of 1.5mm, and the two pole ears of the metal current collector are not coated, and then placed in a 70° oven for 2h to obtain the metal zinc paste battery negative electrode;
[0108] Preparation method of semi-solid electrolyte: 345g of potassium hydroxide with a purity of 95%, 1L of deionized water and 3g of gel (agar) are put into a magnetic stirrer and stirred at a speed of 1500r / min for 45min, then poured into a glass bottle and allowed to stand for 24h to obtain the semi-solid electrolyte;
[0109] The preparation process of the zinc-air battery is as follows: take 2 air electrode carbon sheets (respectively used as the first air electrode carbon sheet and the second air electrode carbon sheet), with the waterproof and breathable membrane of the air electrode carbon sheet facing outward, and use glue to stick the air electrode carbon sheets on the front cover and the back cover (8-grid window cover plate) of the zinc-air battery, and dry them in the shade for 1 hour for use; take 2 positive electrode sheets (respectively used as the first positive electrode sheet and the second positive electrode sheet) and 2 sealing gaskets, respectively use glue to stick them on the front and back outer sides of the shell (9-grid grid structure) of the zinc-air battery, and dry them in the shade for 1 hour for use; put the negative electrode of the metal zinc paste battery cell into the shell of the zinc-air battery and fix it in the card slot position to obtain a shell with a positive electrode and a negative electrode; assemble the front cover with the air electrode carbon sheet, the shell with the positive electrode and the negative electrode, and the back cover with the air electrode carbon sheet in sequence, inject electrolyte, cover the upper cover, and obtain the zinc-air battery.
[0110] Figure 6 The discharge voltage-current-specific energy capacity curve of the zinc-air battery is tested using a newwear tester at room temperature at a constant voltage of 0.9V to observe the changes in current and specific capacity. Figure 6 It can be seen that the voltage curve remains unchanged at 0.9V, and the current curve slowly rises at the beginning, up to 5A. After reaching the highest point, it very slowly drops to 0.15A and the test is stopped. The overall test time is 150H, and the specific capacity is 720mAh / g.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A zinc-air battery, characterized in that: It includes a first air electrode carbon sheet, a first positive electrode sheet, a metal zinc paste battery negative electrode, a second positive electrode sheet, a second air electrode carbon sheet and an electrolyte which are arranged in sequence; The electrolyte is filled in the entire cavity of the zinc-air battery; The negative electrode of the metal zinc paste battery cell comprises a metal current collector and a first zinc electrode and a second zinc electrode respectively arranged on both sides of the metal current collector; The raw material for preparing the first zinc electrode or the second zinc electrode is metal zinc paste; the raw material for preparing the metal zinc paste consists of zinc powder, gel and water; The electrolyte is a semi-solid electrolyte; The first air electrode carbon sheet and the second air electrode carbon sheet both include a waterproof breathable membrane and a support skeleton with a catalyst on the surface, and the waterproof breathable membrane and the support skeleton with a catalyst on the surface are pressed together; The negative electrode of the metal zinc paste battery cell is wrapped by a shell with 9-grid windows; The negative electrode of the metal zinc paste battery cell is a 9-grid grid structure, and the 9-grid grid structure is consistent with the reinforcing ribs of the 9-grid window openings of the shell; It also includes a window cover plate, which includes a front cover, a rear cover and an upper cover; the window cover plate is located at the outermost side of the zinc-air battery, and the front cover and the rear cover of the window cover plate are 8-grid windows.
2. The zinc-air battery according to claim 1, characterized in that The negative electrode of the metal zinc paste battery cell includes two tabs, and the tabs are not wrapped by the shell with 9-grid windows and extend to the outside of the zinc-air battery.
3. The zinc-air battery according to claim 1, characterized in that The inner side section of the shell is provided with side steps and positioning posts for fixing the negative electrode of the metal zinc paste battery cell; The outer side of the shell is provided with a sunken step for placing the first positive electrode sheet and the second positive electrode sheet.
4. The zinc-air battery according to claim 1, characterized in that The first positive electrode sheet and the second positive electrode sheet each include two tabs, and the tabs extend to the outside of the zinc-air battery.
5. The zinc-air battery according to claim 1, characterized in that The method for preparing the negative electrode of the metal zinc paste battery cell comprises the following steps: Mix zinc powder, gel and water to make zinc paste; The zinc paste is coated on both sides of the metal current collector to obtain the negative electrode of the metal zinc paste battery.
6. The zinc-air battery according to claim 5, characterized in that The mass ratio of the zinc powder, gel and water is 30:(1-1.2):(5-6); The gel comprises one or more of food starch glue, polyacrylamide, polyvinyl acetate, sodium carboxymethyl cellulose and polyurethane.
7. The zinc-air battery according to claim 1, characterized in that The preparation method of the semi-solid electrolyte comprises the following steps: After mixing potassium hydroxide, water and gel powder, the mixture is allowed to stand to obtain the semi-solid electrolyte; The mass ratio of the potassium hydroxide, water and gel powder is 345:1000:
3.
8. The zinc-air battery according to claim 7, characterized in that The gel powder comprises one or more of silicon dioxide, water-absorbing resin SAP, agar, potassium alginate, sodium alginate, polyacrylamide and a dispersant.
9. The zinc-air battery according to claim 1, characterized in that The method for preparing the first air electrode carbon sheet or the second air electrode carbon sheet comprises the following steps: mixing carbon powder, graphite, metal oxide and platinum to obtain a mixed catalyst; Mixing the mixed catalyst, polytetrafluoroethylene solution and diluent to obtain a catalyst dispersion; After the support skeleton is immersed in the catalyst dispersion, it is pressed with the waterproof breathable membrane to obtain the first air electrode carbon sheet or the second air electrode carbon sheet.
10. The zinc-air battery according to claim 9, characterized in that The mass ratio of the carbon powder, graphite, metal oxide and platinum is (68-70):(19-20):(10-15):(2-3); The carbon powder is one or more of superconductive carbon powder, activated carbon, carbon black and acetylene black; The mass ratio of the mixed catalyst, the polytetrafluoroethylene solution and the diluent is (65-70): (5-6): (20-30), and the mass concentration of the polytetrafluoroethylene solution is 45%-60%.
Citation Information
Patent Citations
Cylindrical film air electrode and application thereof in zinc-air battery
CN102005578A
Zinc air battery and battery pack
CN106816561A
Solid-state zinc-air battery
CN114744339A
High-power metal air battery
CN114843662A
Air metal battery
JP2016219248A